Desain sensor massa resonator MEMS menggunakan struktur free-free beam - Wangi Pandan Sari (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2021)
MEMS is an integrated electro-mechanical device which the technology has been applied to various applications, one of which is for the fabrication of microsensors, such accelerometers, microsensors for flow sensing, pressure sensing and mass sensing. In the MEMS implementation, there are several approaches and structures that can be used. This study designed a MEMS resonator mass sensor by the means of a mechanical resonator approach with free-free beam structure and actuated electrostatically. The design is expected to produce a MEMS based mass sensor with a high performance.